INTRODUCTION OF ADVANCED PEDAGOGICAL AND INNOVATIVE TECHNOLOGIES IN THE EDUCATIONAL PROCESS AND MECHANISMS TO IMPROVE THE QUALITY OF EDUCATION - Rakhamov Shukhrat Zohirovich; Tairov Oybek Shavkatovich; Abduvoidov Asadbek Akramjon (Modern American Journals, 2025)
The system of introducing pedagogical and innovative technologies into the educational process of new Uzbekistan is based on modern methods and technological trainings that help to increase the effectiveness of teaching students the development of logical, intellectual, creative, critical, independent thinking, the skills of a competitive, mature personality and educate professional qualities needed by the specialist.
Keywords: Pedagogy, innovations, technology, teacher, education, listener, efficiency.